The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1063/1.2837892
|View full text |Cite
|
Sign up to set email alerts
|

Whistler waves in plasmas with magnetic field irregularities: Experiment and theory

Abstract: The properties of whistler waves propagating in a large laboratory magnetoplasma with magnetic field irregularities have been studied. Two types of ambient magnetic field inhomogeneities have been considered: (i) a localized “lenslike” perturbation and (ii) an elongated “ductlike” irregularity. The magnetic field was perturbed by immersing into the plasma, without creating any significant plasma density disturbances, additional current-carrying coils. It has been found that the presence of magnetic field irreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Gushchin et al [2008] have shown with a controlled laboratory plasma experiment that a local magnetic field enhancement can act as a lens, focusing whistler waves and increasing their amplitudes. Magnetic field perturbations of this sort in the magnetosphere can come from MHD oscillations or diamagnetic currents formed at nearby plasma or field gradients.…”
Section: Wave Observationsmentioning
confidence: 99%
“…Gushchin et al [2008] have shown with a controlled laboratory plasma experiment that a local magnetic field enhancement can act as a lens, focusing whistler waves and increasing their amplitudes. Magnetic field perturbations of this sort in the magnetosphere can come from MHD oscillations or diamagnetic currents formed at nearby plasma or field gradients.…”
Section: Wave Observationsmentioning
confidence: 99%
“…The possibility of formation of magnetic field disturbances by electrostatic fields from thunderstorm sources penetrating into the ionosphere has been estimated in [27]. On the other hand, the properties of whistler waves propagating in a large laboratory magnetoplasma with artificially created magnetic field irregularities have been studied in [29][30][31]. Cylindrical magnetic field irregularities were generated by DC-carrying coils in a quasi-uniform plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Cylindrical magnetic field irregularities were generated by DC-carrying coils in a quasi-uniform plasma. It was shown that the non-uniformities of the ambient magnetic field can strongly influence the whistler propagation [29,30] and the VLF antennas' radiation efficiencies [31]. Even a comparatively weak relative magnetic field disturbance of the order of 10% can lead under certain conditions to significant modifications of the whistler waves' pattern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations